2004
DOI: 10.1603/0022-2585-41.5.922
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of <I>Metarhizium anisopliae</I> (Deuteromycetes) on Engorged Larval, Nymphal, and Adult <I>Ixodes scapularis</I> (Acari: Ixodidae)

Abstract: Ixodes scapularis Say adults, nymphs, and larvae were treated with the entomopathogenic fungus Metarhizium anisopliae in a combination of field and laboratory experiments to assess sublethal effects of the fungus on I. scapularis fecundity and body mass. Postengorgement and egg mass weights were 33 and 50% lower, respectively, in adult females treated with M. ansiopliae in the field before engorging on laboratory rabbits. M. anisopliae did not significantly reduce egg mass weight, conversion efficiency, or ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…For example, Ross and Levin (2004) found that some strains of Anaplasma phagocytophilum, the etiologic agent of granulocytic anaplasmosis in humans, affect molting of Ixodes scapularis ticks. Hornbostel et al (2004) found sublethal effects of the entomopathogenic fungus Metarhizium anisopliae on fecundity and body mass of I. scapularis. In cases of mixed infections, these pathogens could potentially influence transmission of other pathogens in the tick by virtue of their effects on tick behavior and survival.…”
Section: Introductionmentioning
confidence: 91%
“…For example, Ross and Levin (2004) found that some strains of Anaplasma phagocytophilum, the etiologic agent of granulocytic anaplasmosis in humans, affect molting of Ixodes scapularis ticks. Hornbostel et al (2004) found sublethal effects of the entomopathogenic fungus Metarhizium anisopliae on fecundity and body mass of I. scapularis. In cases of mixed infections, these pathogens could potentially influence transmission of other pathogens in the tick by virtue of their effects on tick behavior and survival.…”
Section: Introductionmentioning
confidence: 91%
“…is known to be pathogenic to over 200 arthropod species (Samuels et al, 1989), including animal-exploiting ectoparasites: insects, mites and ticks (Samish et al, 2004;Brooks and Wall, 2005;Scholte et al, 2006). This pathogen infects at least 15 tick species (Samish et al, 2008), killing both on-host and off-host stages (Kaaya et al, 1996;Castro et al, 1997;Kaaya, 2000;Kaaya and Hassan, 2000) and causing a variety of sub-lethal effects (Hornbostel et al, 2004;Kirkland et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the field, the spraying plants directly, affects the insect, or the insects become infected by eating or walking on the residue from the surface, varying the amount of infective propagules acquired by the host . This variation can result in a lethal or a sublethal dose, causing death or consequences on insect development, respectively (Royama 1984;Bauer and Nordin 1988b;Giustolin et al 2001;Hornbostel et al 2004). Moreover, according to our results the assessment of mortality without considering the whole cycle of the host, may underestimate the control potential of some entomopathogenic fungi.…”
Section: Resultsmentioning
confidence: 72%